Effects of COVID-19, diabetes mellitus, and cardiovascular diseases on insulin receptor substrate-1 amount in the blood plasma of patients - Tronko, M. D.; Pushkarev, V. V.; Sokolova, L. K.; Cherviakova, S. A.; Belchina, Yu. B.; Kovzun, O. I.; Pushkarev, V. M. (Reports of the National Academy of Sciences of Ukraine, 2021)
Insulin receptor substrate (IRS) is a key adapter protein mediating effects of insulin and insulin-like growth factors (IGF) in cells. IRS-1 is a member of the insulin receptor substrate family, which is associated with tumor initiation and progression. The aim of the study is to determine the level of IRS-1 in the blood of patients (n = 81) with diabetes mellitus and COVID-19. IRS-1 was determined with enzyme-linked immunosorbent assay (ELISA) (Elabscience, USA). The measurements were performed at an optical wavelength of 450 nm. The level of IRS-1 in the blood plasma of patients with COVID-19 was much (from 3.5 to more than 6 times) higher than that in the blood of healthy people. The IRS-1 amounts in COVID-19 patients with diabetes and diabetes + CVD were significantly higher than in patients with COVID-19 without concomitant diseases. The level of IRS-1 in blood plasma may be one of the promising markers of COVID-19.